Inflammatory and lipotoxicity mechanisms in obesity related CKD (2026)
Obesity has been a systemic disease that has been underrecognized for years. Obesity-related chronic kidney disease (Ob-CKD) is a multifaceted disorder that affects patients with CKD to varying degrees. Among the structural changes associated with obesity, obesity-related glomerulopathy (ORG) stands out (glomerular hypertrophy, podocytopathy, mesangial matrix expansion, focal segmental glomerulosclerosis, tubulointerstitial fibrosis, vascular lesions, and tubular atrophy) associated with other kidney diseases. There are direct and indirect mechanisms that affect the kidneys of obese patients. Among the direct mechanisms, several effects may occur: hyperfiltration, activation of the reninangiotensin- aldosterone system (RAAS), inflammation, lipotoxicity, and neurohormonal activation. This is a narrative review that will detail the inflammatory and lipotoxicity mechanisms involved in the genesis of Ob-CKD.